Technology intensification and farmers’ welfare: A case study from Karnataka, a semi-arid state of India - Kapoor, Shreya; Pal, Barun Deb; Singhal, Aditi; Anantha, K. H. (International Food Policy Research Institute, 2020)
Technology adoption has been advocated as an important way to improve agricultural productivity and welfare of farmers in the semi-arid regions across the globe. The Government of Karnataka implemented the Bhoosamrudhi program in four districts of the state (Bidar, Chikballapur, Dharwad, and Udupi) as a pilot project to increase the crop yield and income of smallholder farmers. This program was launched on the theme of technology adoption along with convergence among different departments of agriculture. Farmers have been classified into five categories based on their levels of technology intensification to assess the impact of different levels of technology intensification on their welfare. The research is built on a primary survey conducted in pilot districts of the state in 2018 over a sample of 1,465 farmer households. The results generated using econometric methods of propensity score matching (PSM) and inverse probability weighted with regression adjustment (IPWRA) highlight that the higher the intensification, the higher the net returns to the farmers. The results state that non-adopters would receive a benefit of an additional Rs.3200 per month if they adopt at least one level of technology intensification. Hence, this program turned out to be a successful model for smallholder farmers in semi-arid regions of India. Steps should be taken to maintain and expand the momentum of adoption to ensure food and livelihood security in the economy.